Positive and negative transcriptional elements of the human type IV collagenase gene. - Frisch, S M (1990)
Proteolysis by type IV collagenase (T4) has been implicated in the process of tumor metastasis. The T4 gene is expressed in fibroblasts, but not in normal epithelial cells, and its expression is specifically repressed by the E1A oncogene of adenovirus. We present an investigation of the transcriptional elements responsible for basal, E1A-repressible, and tissue-specific expression. 5'-Deletion analysis, DNase I footprinting, and gel mobility shift assays revealed a strong, E1A-repressible enhancer element, r2, located about 1,650 bp upstream of the start site. This enhancer bound a protein with binding specificity very similar to that of the transcription factor AP-2. A potent silencer sequence was found 2 to 5 bp downstream of this enhancer. The silencer repressed transcription from either r2 or AP-1 enhancer elements and in the context of either type IV collagenase or thymidine kinase (tk) gene core promoters; enhancerless transcription from the latter core promoter was also repressed. Comprising the silencer were two contiguous, autonomously functioning silencer elements. Negative regulation of T4 transcription by at least two factors was demonstrated. mcf-7 proteins specifically binding both elements were detected by gel mobility shift assays; a protein of approximately 185 kDa that bound to one of these elements was detected by DNA-protein cross-linking. The silencer repressed transcription, in an r2 enhancer-tk promoter context, much more efficiently in T4-nonproducing cells (mcf-7 or HeLa) than in T4-producing cells (HT1080), suggesting that cell type-specific silencing may contribute to the regulation of this gene.